Emergence of Functional Flexibility in Infant Vocalizations of the First 3 Months - Jhang, Yuna; Oller, D. Kimbrough (Frontiers in Psychology, 2017)
Functional flexibility, as manifest in the use of any word or sentence to express different affective valences on different occasions, is required in linguistic communication and can be said to be an infrastructural property of language. Early infant vocalizations (protophones), believed to be precursors to speech, occur in the first month and are functionally different from non-speech-like signals (i.e., cries and laughs). Oller et al. (2013) showed that infants by three months used three different protophone types with a full range of affect as manifest in facial expression, from positive to neutral to negative. These differences in affect were also shown to correspond to different illocutionary functions, unlike fixed signals or vegetative sounds, which showed functional rigidity. The present study investigated whether infants show functional flexibility in protophones even earlier than the ages studied by Oller et al (2013). Data were obtained from 6 infants across the first three months. Results showed that as early as the first month, infant protophones were already accompanied by variable facial affect valences and continued to be affectively flexible at the later ages. The present study thus documents the very early emergence of an infrastructural property of human communication.